The Perception, Religiosity, Adherence, and Quality of Life of Diabetes Mellitus Patients in Primary Health Center: Persepsi, Religiusitas, kepatuhan dan Kualitas Hidup Pasien Diabetes Mellitus Di Fasilitas Kesehatan Primer - Aristia, Bella Fevi; Akrom; Saputri, Ginandjar Zukhruf; Mustofa (Jurnal Ilmiah Farmasi, 2024)
Background: Diabetes mellitus is a chronic disease that can overcome complications and decrease quality of life.Objective: The purpose of this study was to determine the effect of counseling religious nuance and pill box on perception, religiosity, quality of life, and adherence in DM patients who get oral antidiabetic in the outpatient of Jetis 1 Primary Health Center, Bantul Regency.Method: This type of research is quasi-experimental, utilizing a pretest and posttest design with a control group. Recruitment of subjects was done by purposive sampling based on exclusion and inclusion criteria with a simple randomization of allocations in order to obtain a sample of 71 people, divided into control (n = 36) and treatment (n = 35) groups. The instrument to assess the success of counseling is the perception questionnaire (B-IPQ), religiosity, and quality of life (EQ5D-3L) that has been validated, while to measure compliance, it is calculated using the pill count method. Statistical analysis using chi square, t test, independent t-test, Wilcoxon test, and Mann-Whitney test with 95% confidence level.Results: The results showed that the treatment group after being given counseling and pill boxes had a better perception (31.37±6.44) than the control group (34.47±7.16) (p<0,05). The treatment group religiosity score was higher (64.28±3.44) compared to the control group (62.17±4.64) (p<0.05). The adherence value of treatment group (96.28±10.32) is greater than that of the control group (88.37±12.39), p<0.05. The majority of patients are still able to walk, perform self-care independently, and carry out daily activities. The highest mean quality of life score was in the treatment group (0.95±0,08) with a mean VAS (77.40±6.31).Conclusion: Based on the results of this study, it can be concluded that there is an influence of giving counseling religious nuance and pill box, which is marked by an increase in perception, religiosity, quality of life, and adherence.Keywords: Diabetes mellitus, perception, religiosity, adherence, quality of life